CORRELATION BETWEEN DENGUE ANTIBODIES IGM AND IGG WITH LYMPHOCYTE COUNT IN PATIENTS WITH SUSPECTED DENGUE FEVER - Priyandari, Damar Ajeng; Yanti, Ni Luh Gede Puspita; Muliawati, Ni Kadek (PT. Jurnal Center Indonesia Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus transmitted to humans through the bite of the Aedes aegypti and Aedes albocpitus mosquitoes. One of the laboratory tests that can help diagnose Dengue fever includes Dengue IgM and IgG Antigens and hematology tests. The number of lymphocytes plays a role in the body's immune system and is one of the parameters found in hematology tests. This study aims to determine the relationship between Dengue IgM and IgG antibodies and the number of lymphocytes in patients suspected of having Dengue fever at the Prodia Sunter Clinical Laboratory for the period 2021-2024. The research method is observational with cross-sectional using secondary data of 104 samples. Data analysis uses Spearman rank. The results of the study showed that most of the suspected Dengue fever patients were male, 56 patients (53.8%) with the highest age at 19-59 years as many as 53 patients (51.0%) and the duration of fever was mostly experienced on the 3rd day of fever 29 patients (27.9%). The results of the Dengue antigen IgM examination in suspected Dengue fever patients were negative for 89 patients (85.6%) and the Dengue antigen IgG was negative for 64 patients (61.5%). The number of lymphocytes was within normal limits for 44 patients (42.3%). The results of the IgM correlation test obtained p = 0.005 with r 0.271, so the hypothesis was accepted, it can be concluded that there is a weak correlation between Dengue IgM antibodies and the number of lymphocytes and the results of the IgG correlation test obtained p = 0.043 with r 0.198, so the hypothesis was accepted, it can be concluded that there is a weak correlation between Dengue IgG antibodies and the number of lymphocytes in suspected Dengue fever patients.